2022
DOI: 10.1177/15269248221132255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Sarcopenia, Malnutrition and Functional status on Postoperative Morbidity Following Liver Transplantation

Abstract: Introduction The effect of sarcopenia, malnutrition, and functional status on immediate post liver transplantation outcome is not well established. Most studies on sarcopenia are related to 1 and 3-year mortality. Studies evaluating the effect of malnutrition are at least a decade old. Project Aims We evaluated the effect of preoperative sarcopenia, malnutrition, and functional status on postoperative length of hospital and ICU stay, incidence of complications, and mortality. Design In this prospective study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Children with PF were significantly more under nutritional support than those without PF. This validates our strong effort to improve the child's nutritional status, avoid malnutrition and counter‐act hepatic osteodystrophy, knowing that LT outcomes are better in the context of good nutritional condition 14–16 . The link between the nutritional condition and bone health has been reported by Kotb et al.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Children with PF were significantly more under nutritional support than those without PF. This validates our strong effort to improve the child's nutritional status, avoid malnutrition and counter‐act hepatic osteodystrophy, knowing that LT outcomes are better in the context of good nutritional condition 14–16 . The link between the nutritional condition and bone health has been reported by Kotb et al.…”
Section: Discussionsupporting
confidence: 71%
“…This validates our strong effort to improve the child's nutritional status, avoid malnutrition and counter-act hepatic osteodystrophy, knowing that LT outcomes are better in the context of good nutritional condition. [14][15][16] The link between the nutritional condition and bone health has been reported by patients with an abnormal dual X-ray scan also had lower weight z-scores before LT. This work underlines moreover that patients who sustain PF have significantly higher levels of total and conjugated bilirubin at the moment of LT, suggesting that cholestatic patients are more prone to have PF.…”
Section: Nutritional Supportmentioning
confidence: 99%
“…Our retrospective, single-center study indicates that the presence of sarcopenia in cirrhotic patients is a strong and independent risk factor for short-term mortality after TIPS placement. We were able to present a PMI cutoff value of 4.4 cm 2 /m 2 for males and 3.2 cm 2 /m 2 for females in defining sarcopenia and our results demonstrate that sarcopenia by this definition is associated with an increased risk of short-term 1-year mortality (hazard A growing body of literature supports the association between sarcopenia and mortality in various types of malignancies [19] and liver or renal transplantation [20]. A study on 200 patients undergoing living donor liver transplantation reported that patients with high intramuscular adipose tissue content and low PMI had lower overall survival rates compared to those with normal values [21].…”
Section: Discussionmentioning
confidence: 64%
“…A growing body of literature supports the association between sarcopenia and mortality in various types of malignancies [19] and liver or renal transplantation [20]. A study on 200 patients undergoing living donor liver transplantation reported that patients with high intramuscular adipose tissue content and low PMI had lower overall survival rates compared to those with normal values [21].…”
Section: Discussionmentioning
confidence: 99%